Identification of an Aurora kinase inhibitor specific for the Aurora B isoform - Xie, Hua (2012)
Aurora kinases play an important role in chromosome alignment, segregation, and cytokinesis during mitosis. In the present study, we used a ligand-docking method to explore the novel scaffold of potential Aurora B inhibitors. One thousand compounds from our in-house compound library were screened against the Aurora B structure and one compound, (E)-3-((E)-4-(benzo[d][1,3]dioxol-5-yl)-2-oxobut-3-en-1-ylidene)indolin-2-one (designated herein as HOI-07) was selected for further study. HOI-07 potently inhibited in vitro Aurora B kinase activity in a dose-dependent manner, without obvious inhibition of another 49 kinases, including Aurora A. This compound suppressed Aurora B kinase activity in lung cancer cells, evidenced by the inhibition of the phosphorylation of histone H3 on Ser10 in a dose- and time-dependent manner. This inhibition resulted in apoptosis induction, G2/M arrest, polyploidy cells, and attenuation of cancer cell anchorage-independent growth. Moreover, knocking down the expression of Aurora B effectively reduced the sensitivity of cancer cells to HOI-07. Results of an in vivo xenograft mouse study showed that HOI-07 treatment effectively suppressed the growth of A549 xenografts, without affecting the body weight of mice. The expression of phospho-histone H3, phospho-Aurora B, and Ki-67 was also suppressed in the HOI-07 treatment group. Taken together, we identified HOI-07 as a specific Aurora B inhibitor, which deserves further investigation.